Diet, occupational exposure and early asthma incidence among bakers, pastry makers and hairdressers - Rémen Thomas; Acouetey Dovi-Stéphanie; Paris Christophe; Zmirou-Navier Denis (BMC, 2012)
Abstract Background The natural history of occupational asthma (OA) is influenced by many determinants. This study aims to assess the combined roles of personal characteristics, including occupational exposure and nutritional habits, on the incidence of OA during the first years at work. Methods A nested case-control study was conducted within a retrospective cohort of young workers in the bakery, pastry-making and hairdressing sectors. Cases were subjects diagnosed as 'confirmed' or 'probable' OA consecutively to a medical visit (N = 31). Controls were subjects without OA (N = 196). Atopy was defined after blood specific IgE analysis, based on the PhadiatopTM test. Occupational exposure was characterized by standardized questionnaires and diet patterns by a food frequency questionnaire. Results Among bakers and pastry-makers, only atopy is an independent risk factor of OA (OR = 10.07 95%CI [2.76 - 36.65]). Among hairdressers, several variables are associated with OA. Body mass index (unit OR = 1.24 [1.03 - 1.48]) and the score of exposure intensity (unit OR = 1.79 [1.05 - 3.05]) are independent predictors of OA, but the role of atopy is weak (OR = 4.94 [0.66 - 36.75]). Intake of vitamin A is higher among hairdressers cases (crude p = 0.002, adjusted p = 0.01 after control for body mass index and atopy); the same observation is made for vitamin D (crude p = 0.004, adjusted p = 0.01). Conclusion This study suggests that the influence of several factors on the incidence of OA, including dietary vitamins, might vary across exposure settings.